2021
DOI: 10.21203/rs.3.rs-120819/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Follow-up of COVID-19 Recovered Patients with Mild Disease

Abstract: COVID-19 may manifest as mild, moderate or severe disease with each grade of severity having its own features and post-viral implications. With the rising burden of the pandemic, it is vital to identify not only active disease but any post-recovery complications as well.This study was conducted with the aim of identifying the presence of post-viral symptomatology in patients recovered from mild COVID-19 disease. Presence or absence of eleven post viral symptoms was recorded and we found that eight of the eleve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Blomberg et al found that young, home-isolated adults with mild COVID-19 are at risk of long-lasting dyspnea and cognitive symptoms ( 31 ). Kashif et al also reported various post-viral sequelae, the most common being fatigue, in mild-COVID-19 recovered patients ( 32 ).…”
Section: Introductionmentioning
confidence: 97%
“…Blomberg et al found that young, home-isolated adults with mild COVID-19 are at risk of long-lasting dyspnea and cognitive symptoms ( 31 ). Kashif et al also reported various post-viral sequelae, the most common being fatigue, in mild-COVID-19 recovered patients ( 32 ).…”
Section: Introductionmentioning
confidence: 97%
“…Clinical manifestations may range from the most common symptoms such as fever, cough, dyspnea, myalgia, and fatigue to respiratory distress or respiratory failure [4]. Additionally, most of the patients recovered from COVID-19 present a wide variety of persistent symptoms, even if mild severity [5,6].…”
Section: Introductionmentioning
confidence: 99%